2015
DOI: 10.1111/bjd.13441
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based topical treatments for tinea cruris and tinea corporis: a summary of a Cochrane systematic review

Abstract: Tinea cruris and tinea corporis are common fungal infections. Most can be treated with a variety of topical antifungals. This review aimed to assess the evidence for the effectiveness and safety of topical treatments for tinea cruris and tinea corporis. Searches included the Cochrane Skin Group Specialised Register, CENTRAL in The Cochrane Library, Medline, Embase, LILACS and ongoing trials registries (August 2013). One hundred and twenty-nine randomized controlled trials (RCTs) with 18 086 participants evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 95 publications
(138 reference statements)
0
29
0
5
Order By: Relevance
“…Zuuren and Fedorowics reported that combination of Azoles with Corticosteroids were slightly more effective than azoles for clinical cure in tineacruris and tineacoporis but there was no statistically significant difference with regards to mycological cure [11]. Havlickova and Friedrich recommended combination therapy of topical antifungal with a topical corticosteroids for tinea infection associated with inflammation [12].…”
Section: Drug Prescribing Patternmentioning
confidence: 99%
“…Zuuren and Fedorowics reported that combination of Azoles with Corticosteroids were slightly more effective than azoles for clinical cure in tineacruris and tineacoporis but there was no statistically significant difference with regards to mycological cure [11]. Havlickova and Friedrich recommended combination therapy of topical antifungal with a topical corticosteroids for tinea infection associated with inflammation [12].…”
Section: Drug Prescribing Patternmentioning
confidence: 99%
“…Moreover, topical steroids can be transiently effective on mycological lesions, by resolving the pruritus and alleviating the burning sensation and inflammation. 11 Dermatological conditions, including dermatophytoses, are common in clinical practice. 12 In France and the United Kingdom, most patients with skin lesions first consult their GP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that corticosteroids may interfere with the therapeutic action of the antifungal agent, or increase fungal growth as a result of decreased localised immune response . However, a number of studies have demonstrated that there is no significant difference in the rate of mycological cure between antifungal‐corticosteroid combination therapy and antifungal monotherapy . Moreover, antifungal‐corticosteroid combination therapy demonstrates more rapid therapeutic activity, and has been shown to be more effective in achieving clinical cure (the absence of symptoms such as erythema and pruritus) than topical antifungal therapy alone .…”
Section: Antifungal‐corticosteroid Combination Therapymentioning
confidence: 99%